2011 IEEE International Conference on Multimedia and Expo 2011
DOI: 10.1109/icme.2011.6011994
|View full text |Cite
|
Sign up to set email alerts
|

Photosense: Make sense of your photos with enriched harmonic music via emotion association

Abstract: This paper proposes a novel audiovisual presentation system, called PhotoSense, to enrich photo navigation experience by associating emotionally harmonic music with a given photo collection. Different from many conventional photo visualization systems which predominantly focus on the visual elements for presentation, we explore both visual and aural perspectives which can enhance the browsing experience from each other. This is achieved by building an emotion space shared by visual and aural domains, and a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The emotion detected through the stroke behavior 31:24 Y. Gao et al could be used to tag the stored material and to identify clusters of stored information (music and photos) that reflect similar emotions [Su et al 2011]. Such metatagging could also be used to facilitate crowdsourcing of media information and to build better recommendation systems [Brew et al 2010].…”
Section: The Use Of Affective Touch Recognition In Other Applicationsmentioning
confidence: 99%
“…The emotion detected through the stroke behavior 31:24 Y. Gao et al could be used to tag the stored material and to identify clusters of stored information (music and photos) that reflect similar emotions [Su et al 2011]. Such metatagging could also be used to facilitate crowdsourcing of media information and to build better recommendation systems [Brew et al 2010].…”
Section: The Use Of Affective Touch Recognition In Other Applicationsmentioning
confidence: 99%
“…(4) Sound effects (ST): Previous literature [12,71] found that playing background sounds related to photos could enhance the atmosphere of the story and make the listener and speaker feel immersed in the scene, thereby enhancing the effect of communication. Different types of background sounds for different photos were provided in the probe (e.g., old songs of the same age as the photo of a park, the sound of waves and seagulls for the photo on the beach, and the cries of hawkers for a market photo).…”
Section: Ar Probe Designmentioning
confidence: 99%
“…They separately extracted hand-crafted features, learned emotion classifiers, and composited images and music based on the predicted emotions. Many methods follow this pipeline [34,48,53,61,86]. They (1) extracted more discriminative emotion features, such as low-level color [9,34,48,53,61] and mid-level principlesof-art [86] for image; (2) employed different emotion representation models, from categorical states [9,34,53,61] to dimensional space [48,86]; (3) correspondingly learned different classifiers, from Support Vector Machine [9], Naive Bayes, and Decision Tree [53] to Support Vector Regression [86]; and (4) used different composition strategies to match image and music, from emotion category comparison [9,34,53,61] to Euclidean distance [48,86].…”
Section: Related Workmentioning
confidence: 99%
“…Such emotion-based matching is essential for various applications [57], such as affective cross-modal retrieval, emotion-based multimedia slideshow, and emotion-aware recommendation systems. The early emotion-based matching methods mainly employ a shallow pipeline [9,34,48,53,61,86], i.e. extracting hand-crafted features and training matching classifiers (or training emotion classifiers for both modalities and then learning matching similarities).…”
Section: Introductionmentioning
confidence: 99%